Normative range of various serum hormonal parameters among Indian women of reproductive age: ICMR-PCOS task force study outcomeResearch in context - Mohd Ashraf Ganie; Subhankar Chowdhury; Vanita Suri; Beena Joshi; Prasanta Kumar Bhattacharya; Sarita Agrawal; Neena Malhotra; Rakesh Sahay; Puthiyaveettil Khadar Jabbar; Abilash Nair; Roya Rozati; Amlin Shukla; et al. (Elsevier, 2023)
Summary: Background: The hormonal profile varies considerably with age, gender, ethnicity, diet or physiological state of an individual. Limited population-specific studies have studied the variations in hormonal parameters among apparently healthy women. We aimed to analyse the biological reference interval for various hormonal parameters in the reproductive-aged healthy Indian women. Methods: Out of 3877 participants that were clinically evaluated, 1441 subjects were subjected to laboratory investigations. All participants underwent a detailed clinical, biochemical and hormonal profiling. The hormone analysis was carried out at a single centre using a uniform methodology. Among the participants evaluated for biochemical and hormonal parameters, subjects that presented any abnormal profile or had incomplete investigations (n = 593) were excluded for further analysis. Findings: The mean age (±SD) of the subjects retained in the final analysis (n = 848) was 29.9 (±6.3) years. In the present study, the biological reference interval (2.5th-97.5th centile) observed were: serum T4: μg/dL (5.23-12.31), TSH: μg/mL (0.52-4.16) and serum prolactin: ng/mL (5.13-37.35), LH: mIU/mL (2.75-20.68), FSH: mIU/mL 2.59-15.12), serum total testosterone: ng/mL (0.06-0.68), fasting insulin: mIU/mL (1.92-39.72), morning cortisol: μg/dL (4.71-19.64), DHEAS:μg/dL (50.61-342.6) and SHBG: nmol/L (21.37-117.54). Unlike T4, TSH, LH, and E2, the biological reference interval for prolactin, FSH, testosterone, C-peptide insulin and DHEAS varied when the subjects were stratified by age (p < 0.05). The comparative analysis showed marginal differences in the normative ranges for the hormones analysed among different populations. Interpretation: Our first large composite data on hormonal measures will benefit future endeavours to define biological reference intervals in reproductive-aged Indian women. Funding: The study was financially supported by the grant-in-aid from ICMR vide file No:5/7/13337/2015-RBMH.